2005
DOI: 10.1097/01.mpg.0000153887.19429.70
|View full text |Cite
|
Sign up to set email alerts
|

Using the Concept of Food Based Dietary Guidelines to Develop an Optimized Mixed Diet (OMD) for German Children and Adolescents

Abstract: Exact menus and food amounts are a prerequisite to ascertain nutrient adequacy of FBDG. The OMD demonstrates that a single diet concept with a core of quantified food groups can be adequate for age groups between 1 and 18 years within a country, such as Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0
10

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 37 publications
2
110
0
10
Order By: Relevance
“…However, in a recent evaluation of the DONALD Study, we could show a trend towards RTEC breakfasts (Alexy et al, 2010 (under review)), but with a low effect of RTECs and mueslis on whole grain intake, as shown by the present evaluation. Total grain intake corresponded well with the German FBDG for children and adolescents, especially in the younger age groups (Kersting et al, 2005). The German FBDG recommend between 120 g grain per day for 2-3 year olds and 350 g for 15-to 18-year-old males.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, in a recent evaluation of the DONALD Study, we could show a trend towards RTEC breakfasts (Alexy et al, 2010 (under review)), but with a low effect of RTECs and mueslis on whole grain intake, as shown by the present evaluation. Total grain intake corresponded well with the German FBDG for children and adolescents, especially in the younger age groups (Kersting et al, 2005). The German FBDG recommend between 120 g grain per day for 2-3 year olds and 350 g for 15-to 18-year-old males.…”
Section: Discussionsupporting
confidence: 69%
“…The Dietary Guidelines for Americans recommend the consumption of at least half the recommended grain serving as whole grains from over two years of age at each calorie levels (U.S. Department of Health and Human Services, 2005). The German FBDG for children and adolescents also recommend that half the amount of grains should be consumed as whole grain (Kersting et al, 2005). In the British FBDG a high intake of starchy food and the predominant choice of whole grain varieties is recommended (British Nutrition Foundation (BNF), 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the OMD (18) and FGP recommendations (19) one glass of 100 % fruit juice (200 ml) can be counted as one portion of fruit. Median intake of fruit and vegetable juice was 100 ml/d in girls and boys of both age groups (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Weight was measured with an electronic scale to the nearest 0?1 kg, and height was measured with a telescopic stadiometer to the nearest 0?1 cm. BMI was (18) .…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…In the present study we assessed the dietary intake of the TEENDIAB children, and measured it against the German Dietary Reference Intakes on the nutrient level (13) and against the Optimized Mixed Diet recommendations developed by the Research Institute of Child Nutrition in Dortmund (14,15) on the food level. Furthermore, we compared the intake data of the TEENDIAB children with those of a representative sample of children aged 12 years from the EsKiMo study, the nutrition module of KiGGS, the German Health Interview and Examination Survey of Children and Adolescents (16) .…”
mentioning
confidence: 99%